Pengaruh Model Discovery Learning Terhadap Aktivitas dan Hasil Belajar Kognitif Peserta Didik - Oktriviani, Shella; Marpaung, Rini Rita T.; Yolida, Berti (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2019)
This study aims to determine the effect of discovery learning on activities and cognitive learning outcomes students of class VIII SMPN 1 Lawang Kidul in